An efficient synthesis of tetraazapentacenes - Tverskoy, Olena; Rominger, Frank; Peters, Anastasia; Himmel, Hans-Jörg; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2011)
Organic electronics on demand? The palladium-catalyzed coupling of aromatic ortho-diamines with substituted dichloroquinoxalines furnishes N,N-dihydrotetraazaacenes, which were oxidized by MnO2 into the corresponding tetraazapentacenes (see structures; N blue, Cl green, Si yellow). The modular synthesis of these acenes allows the introduction of any substituent by choice of the proper quinoxaline derivative.
Dedicated to Professor Günter Helmchen and Professor Rolf Gleiter
Gesehen am 30.11.2022